2022
DOI: 10.1186/s41927-022-00276-w
|View full text |Cite|
|
Sign up to set email alerts
|

Muscle B mode ultrasound and shear-wave elastography in idiopathic inflammatory myopathies (SWIM): criterion validation against MRI and muscle biopsy findings in an incident patient cohort

Abstract: Background B mode ultrasound (US) and shear wave elastography (SWE) are easily accessible imaging tools for idiopathic inflammatory myopathies (IIM) but require further validation against standard diagnostic procedures such as MRI and muscle biopsy. Methods In this prospective cross-sectional study we compared US findings to MRI and muscle biopsy findings in a group of 18 patients (11 F, 7 M) with active IIM (dermatomyositis 6, necrotising autoimmu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 41 publications
0
14
0
1
Order By: Relevance
“…Similar greater sensitivity of sonoelastography versus grayscale US for early stages of tendinopathy have been reported in the Achilles, quadriceps, biceps, supraspinatus, and other tendons 9,14–17 . Sonoelastography has also been applied to osteoarthritic cartilage, the transverse ligament in carpal tunnel syndrome, myopathies, ligaments, rheumatoid synovitis, methotrexate hepatotoxicity (important in rheumatology), meniscal disease, trigger finger, and musculoskeletal tumors with similar changes in elasticity of the relevant tissue with variable sensitivity and specificity for pathology versus alternative imaging methods 14–25 …”
mentioning
confidence: 86%
See 3 more Smart Citations
“…Similar greater sensitivity of sonoelastography versus grayscale US for early stages of tendinopathy have been reported in the Achilles, quadriceps, biceps, supraspinatus, and other tendons 9,14–17 . Sonoelastography has also been applied to osteoarthritic cartilage, the transverse ligament in carpal tunnel syndrome, myopathies, ligaments, rheumatoid synovitis, methotrexate hepatotoxicity (important in rheumatology), meniscal disease, trigger finger, and musculoskeletal tumors with similar changes in elasticity of the relevant tissue with variable sensitivity and specificity for pathology versus alternative imaging methods 14–25 …”
mentioning
confidence: 86%
“…The low cost, convenience, noninvasive nature, lack of ionizing radiation, direct relevance to palpable anatomy, point‐of‐care applicability, and increasing number of applications indicate that US will only increase in use in musculoskeletal medicine 1–4 . Sonoelastography is another powerful method available to observe the musculoskeletal system, and appears particularly valuable in detecting early tendinopathies, areas of myopathy suitable for biopsy, pursuing complaints of localized musculoskeletal pain, analyzing soft tissue masses, and research applications in musculoskeletal medicine 14–25 . Shear wave elastography in particular permits rapid quantitative assessments of musculoskeletal structures and will be particularly valuable at the beside, in research studies and clinical trials, and in monitoring disease presence, progression, and response to therapy, especially in muscle and tendon disease.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Following publication of the original article [ 1 ], it was reported that there was an error in the caption for Fig. 1A .…”
Section: Correction To: Bmc Rheumatology (2022) 6:47 101186/s41927-02...mentioning
confidence: 99%